2009
DOI: 10.1159/000228245
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Post-Pancreaticoduodenectomy Bleeding and Finding an Innovative Approach to Treatment

Abstract: Background: This study is to determine the risk factors and outcome for post-pancreaticoduodenectomy bleeding, and to assess the roles of surgery and intravascular intervention in its management. Methods: Post-pancreaticoduodenectomy data of 628 patients were analyzed with regards to post-pancreaticoduodenectomy bleeding. Results: Post-pancreaticoduodenectomy bleeding occurred in 58 patients (9.2%) and led to death in 23 patients. Pancreatic leakage and intra-abdominal abscess were independent risk factors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 43 publications
(60 reference statements)
3
26
1
Order By: Relevance
“…25,26 Pancreatic fistula and intra-abdominal abscess may erode the arterial wall. [27][28][29] In this study, the incidence rates of these two complications were 74.3% and 57.1%, respectively. Since they have been proven to be risk factors of postoperative massive hemorrhage, 28,29 early identification and management of these complications may help to prevent pseudoaneurysm formation after pancreatic surgery.…”
Section: Discussionmentioning
confidence: 50%
“…25,26 Pancreatic fistula and intra-abdominal abscess may erode the arterial wall. [27][28][29] In this study, the incidence rates of these two complications were 74.3% and 57.1%, respectively. Since they have been proven to be risk factors of postoperative massive hemorrhage, 28,29 early identification and management of these complications may help to prevent pseudoaneurysm formation after pancreatic surgery.…”
Section: Discussionmentioning
confidence: 50%
“…Our finding is consistent with the literatures by Sato et al [21], Yekebas et al [22] and Choi et al [38] who reported a significantly elevated risk of DPPAB in patients with pancreatic fistula. Wei et al [45] confirmed that pancreatic leakage and intra-abdominal abscess are independent risk factors for post-PD bleeding. Hence, any procedure that can prevent the formation of pancreatic fistula or intra-abdominal abscess can decrease the prevalence of DPPAB.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreaticoduodenectomy (PD) is a complex surgery for the treatment of malignant and selected benign diseases originated from periampullary region. Although the mortality of PD has decreased significantly over the last decade, postoperative morbidity remains at 30–50% even in many high volume centers . Among all the complications, post‐PD hemorrhage (PPH) is the most lethal one, with the incidence ranging from 3% to 20%, but related mortality being as high as 20% to 50% …”
Section: Introductionmentioning
confidence: 99%